From "colonial reciprocity" to international supremacy: Scottish chartered accountancy and its "discourse of superiority" in context, 1854 to the present. (February 2014) - McKinstry, Sam
This article examines developments in the history of the Institute of Chartered Accountants of Scotland (ICAS) and its predecessor professional bodies, in an attempt to shed fresh light on the means by which the Institute has attained the position of considerable power, repute and international influence that it occupies today. It shows that, over its history, ICAS has been responsible for creating and maintaining a discourse, in a Foucauldian sense, which has asserted the superiority of the CA qualification over other professional accounting qualifications both nationally and internationally. It is argued that this discourse first arose out of a crisis facing the Institute's predecessor bodies in 1853, continuing afterwards and then reappearing at further pivotal points in the Institute's history. The study utilizes the Foucauldian concepts of discourse, power/knowledge, discontinuity and exclusion in its arguments, showing how these relate to fluctuations in the, at times, parallel discourse concerning Scots national identity that has also been in circulation, concluding with an evaluation of the usefulness of a Foucauldian approach.